Atmospheric drivers affect crop yields in Mozambique - Takele, Robel; Buizza, Roberto; Dell'Acqua, Matteo (Frontiers in Climate, 2023)
Climate change has been inducing variations in the statistics of both the large-scale weather patterns and the local weather in many regions of the world, and these variations have been affecting several human activities, agriculture included. In this work we look at the links between large-scale weather patterns and local weather, and agriculture, with a specific regional focus on Mozambique over the period 1981-2019. Firstly, we document how climate change has been affecting the statistics of largescale weather patterns. Secondly, we investigate the links between large-scale weather patterns and local weather. Finally, we link up climate, weather, and yield of cereals in Mozambique to assess what is the relation between large-scale patterns and local agronomic outputs. Results indicate that over Mozambique the crop season warmed substantially, consistently with climate change-induced global warming, and the rainy season has become drier and shorter, with precipitation concentrated in fewer, more intense events. These changes in the local weather have been linked to variations in the statistics of large-scale weather patterns that characterize the (large-scale) atmospheric flow over the region. The link between weather variations and crop yield was assessed by applying a multiple linear regression (MLR) model with crop yield data as the response variable and climate drivers as predictors to estimate the climate impact on country-level yield. Results indicate a negative impact on yield associated with climate change, with average yield losses of 20% for rice and 8% for maize over the analyzed period . This negative impact suggests that, at country scale, further future warming during the growing season may offset some of the cereal yield gains from technological advances.